Pharmacoinformatics and uplc-qtof/esi-ms-based phytochemical screening of combretum indicum against oxidative stress and alloxan-induced diabetes in long–evans rats - Forid, M. S.; Rahman, M. A.; Aluwi, M. F. F. M.; Uddin, M. N.; Roy, T. G.; Mohanta, M. C.; Huq, A. K. M. M.; Zakaria, Z. A. (MDPI - Open Access Publishing, 2021)
This research investigated a UPLC-QTOF/ESI-MS-based phytochemical profiling of Com-bretum indicum leaf extract (CILEx), and explored its in vitro antioxidant and in vivo antidiabetic effects in a Long–Evans rat model. After a one-week intervention, the animals’ blood glucose, lipid profile, and pancreatic architectures were evaluated. UPLC-QTOF/ESI-MS fragmentation of CILEx and its eight docking-guided compounds were further dissected to evaluate their roles using bioinformatics-based network pharmacological tools. Results showed a very promising antioxidative effect of CILEx. Both doses of CILEx were found to significantly (p < 0.05) reduce blood glucose, low-density lipoprotein (LDL), and total cholesterol (TC), and increase high-density lipoprotein (HDL). Pancreatic tissue architectures were much improved compared to the diabetic control group. A computational approach revealed that schizonepetoside E, melianol, leucodelphinidin, and ar-butin were highly suitable for further therapeutic assessment. Arbutin, in a Gene Ontology and PPI network study, evolved as the most prospective constituent for 203 target proteins of 48 KEGG pathways regulating immune modulation and insulin secretion to control diabetes. The fragmentation mechanisms of the compounds are consistent with the obtained effects for CILEx. Results show that the natural compounds from CILEx could exert potential antidiabetic effects through in vivo and computational study.